Sunscreens as a prevention of the photoaging - Paulina Kostrzewska; Amanda Mandera; Anna Pawlikowska; Ewa Szuster (Kazimierz Wielki University, 2020)
Proper aging is genetically determined, progresses over time and cannot be stopped. External aging, on the other hand, is caused by factors affecting the organism from the outside, such as permanent exposure to the sun, stress, diet. This factors are modifiable. Exposure to UV radiation is one of the main factors responsible for skin aging. It causes also skin cancers like melanoma, basal cell cancer and sunburns. In this review, we have discussed the skin aging mechanisms and using sunscreens as a prevention of the photoaging and another serious effects like skin cancer. Sun Protection Factor (SPF) is used to describe the sun protection ability and it measures the fraction of sunburn-producing UV rays that reach the skin. Sunscreens with high SPF protect the skin by absorbing or reflection of harmful UV radiation from the sun. They minimize damaging effects and prevent sunburns, loss of elasticity and wrinkles.